POLITIK HUKUM EKONOMI KERAKYATAN BERBASIS ORANG ASLI PAPUA DALAM KONSEP OTONOMI KHUSUS PAPUA (Fakultas Hukum Dehasen, 2017)
Populist economic development in the era of the Papua Special Autonomy aims to increase community participation in various activities especially in the field of economic development. Dnature of this context, if we want to talk 'prosperity and welfare of indigenous Papuans, we first formulate the proper democratic economy with social and cultural life of indigenous Papuan people. The presence Perdasus No. 18 No. 18 of 2008 on Kerakyataan Based Economy has given a clear formulation of improving the lives of the indigenous people of Papua especially in developing themselves in the micro and macro level.